Employment of Rainwater Infiltration Wells for Flood Mitigation - Patti Rajunai; Surapaninn Loh (Akademi Sertifikasi Profesi Internasional, 2023)
This region holds considerable attraction for tourists. The extensive expansion of tourist attractions renders this hamlet susceptible to waterlogging during the rainy season, attributable to insufficient water infiltration, resulting in frequent occurrences of waterlogging. The community also encounters the issue of inadequate management of spring water supplies. The approach we proposed involved the implementation of infiltration wells. This well serves as a receptacle for rainfall that either descends or flows from upstream and is then collected into a reservoir (SPAH). The Rainwater Harvesting System (SPAH) is a method for utilizing rainwater for everyday requirements. The fundamental premise is that the water entering the infiltration well is channeled to the reservoir. This initiative involves the establishment of infiltration wells to facilitate the acquisition of clean water for communities while mitigating concerns of waterlogging during the rainy season. We aim to assist the community by providing a complimentary clean water supply.